1990
DOI: 10.1212/wnl.40.3_part_1.413
|View full text |Cite
|
Sign up to set email alerts
|

Anterior temporal lobectomy for complex partial seizures

Abstract: We report evaluation and results in 100 patients who had undergone anterior temporal lobectomy for intractable complex partial seizures. Average follow-up was 9.0 years (range, 2 to 21 years). In the 2nd postoperative year, 63% were seizure free, 16% were significantly improved, and 21% were considered not significantly improved. Mean number of seizures in the last group was 27% of preoperative levels. Surgical results did not change significantly in subsequent postoperative years; good outcomes tended to pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(42 citation statements)
references
References 0 publications
4
38
0
Order By: Relevance
“…Most studies (1)(2)(3) evaluates surgical outcome at a fixed time. Rasmussen (43) noted that after surgery for epilepsy, patients may experience some seizures in the first few months or years, but the seizures later remit.…”
mentioning
confidence: 99%
“…Most studies (1)(2)(3) evaluates surgical outcome at a fixed time. Rasmussen (43) noted that after surgery for epilepsy, patients may experience some seizures in the first few months or years, but the seizures later remit.…”
mentioning
confidence: 99%
“…Temporal lobe resection leads to improvement in seizure control or abolition of seizures in 60-80% of selected cases (1)(2)(3)(4). In the minority who do not benefit, the reasons are often unclear.…”
mentioning
confidence: 99%
“…First, IEDs may be completely absent despite definite focal epilepsy as captured by ictal recordings in nearly 20% of known persons with epilepsy [11,12]. If the epileptogenic region is either too small (b6 cm 3 ), too deep (depth of sulcus), or located in an "invisible" region such as orbitofrontal cortex or the interhemispheric fissure, discharges may not be seen on the surface EEG.…”
Section: Pitfalls Of the Interictal Eegmentioning
confidence: 99%
“…It has shown the best outcome [35,36] in the only randomized prospective controlled study for assessing temporal lobectomy [37]. Studies have found that 74 and 92% of patients with interictal unilateral anterior temporal spikes became seizure free or significantly improved after anteromedial temporal resection [11,38]. In another study, a positive outcome was noted in patients with more than 90% of IEDs ipsilaterally [39].…”
Section: Mesial Temporal Sclerosismentioning
confidence: 99%